On a semitopological semigroup $\boldsymbol{B}_{ω}^{\mathscr{F}}$ when a family $\mathscr{F}$ consists of inductive non-empty subsets of $ω$ - O. V. Gutik; M. S. Mykhalenych (Математичні Студії, 2023)
Let $\boldsymbol{B}_{ω}^{\mathscr{F}}$ be the bicyclic semigroup extension for the family $\mathscr{F}$ of ${ω}$-closed subsets of $ω$ which is introduced in \cite{Gutik-Mykhalenych=2020}. We study topologizations of the semigroup $\boldsymbol{B}_{ω}^{\mathscr{F}}$ for the family $\mathscr{F}$ of inductive ${ω}$-closed subsets of $ω$. We generalize Eberhart-Selden and Bertman-West results about topologizations of the bicyclic semigroup \cite{Bertman-West-1976, Eberhart-Selden=1969} and show that every Hausdorff shift-continuous topology on the semigroup $\boldsymbol{B}_{ω}^{\mathscr{F}}$ is discrete and if a Hausdorff semitopological semigroup $S$ contains $\boldsymbol{B}_{ω}^{\mathscr{F}}$ as a proper dense subsemigroup then $S\setminus\boldsymbol{B}_{ω}^{\mathscr{F}}$ is an ideal of $S$. Also, we prove the following dichotomy: every Hausdorff locally compact shift-continuous topology on $\boldsymbol{B}_{ω}^{\mathscr{F}}$ with an adjoined zero is either compact or discrete. As a consequence of the last result we obtain that every Hausdorff locally compact semigroup topology on $\boldsymbol{B}_{ω}^{\mathscr{F}}$ with an adjoined zero is discrete and every Hausdorff locally compact shift-continuous topology on the semigroup $\boldsymbol{B}_{ω}^{\mathscr{F}}\sqcup I$ with an adjoined compact ideal $I$ is either compact or the ideal $I$ is open, which extent many results about locally compact topologizations of some classes of semigroups onto extensions of the semigroup $\boldsymbol{B}_{ω}^{\mathscr{F}}$.